SOCIAL RESPONSIBILITY IN UKRAINE: PUBLIC AND CORPORATE ASPECTS - Romaniuk , M.D.; Romaniuk , T.M. (The actual problems of regional economy development, 2023)
The current state of social and economic development in Ukraine is characterized by the need to develop and dissemination of social responsibility practices both at the level of companies and at the level of the business community and society as a whole. The main priority at this should be ensuring mutually beneficial interests of business and society. The main goals of business in the social aspect should be promotion of sustainable social development. Social responsibility of business foresees a certain level of development of an enterprise and a voluntary response to social problems of society, such aspects as compliance with ethical standards, balanced consideration of stakeholders' interests, participation in community development and adherence to the principles of sustainable development. The article examines the essence and peculiarities of development and implementation of social responsibility and corporate social responsibility, in particular, their levels, types of manifestation and measures of social policy in Ukraine. It has been found out that domestic enterprises mostly implement such elements of social responsibility as labor relations, human rights, labor protection, fair operating practices, environmental protection, and work with stakeholders (partners, consumers, and government agencies). The current state and problems of implementation of corporate social responsibility by domestic enterprises have been characterized. It has been established that corporate social responsibility is carried out in the following main forms: production of quality products and services for consumers; creation of attractive jobs, payment of legal salaries and investment in human capital development; unconditional compliance with legal requirements; building good faith relations with all stakeholders; taking into account public expectations and generally accepted ethical norms in business practices; contribution to the formation of civil society through partnership programs and projects of development. The directions of development of social responsibility of business in Ukraine have been substantiated.